Organizational Rightsizing Analysis of the Existence of the DPD RI Office in the Provincial Capital of South Sumatera - Arief Maulana; Ardiyan Saptawan; Nurmah Semil (Universitas Teuku Umar, 2023)
This study aims to explain the effectiveness of organizational rightsizing of the DPD RI Office in the Capital City of South Sumatra Province as a supporting system for DPD RI members in carrying out their roles as regional representatives. The research method used is a qualitative method with a descriptive approach. Using structured interviews, participant observation, and documentation, data was collected. Meanwhile, data validation uses triangulation techniques. Selecting informants believed to comprehend the research problem to yield primary data (purposive sampling). Data analysis was carried out using the interactive model of Miles, Huberman and Saldana (2014). The results showed that 2 of the three aspects of the organizations rightsizing could have gone better. From the aspect of strategic policy, it has reflected a picture of the conditions and conditions to be realized in 2020-2024. From the aspect of the division of organizational units, the Office has not relied on the principles of rightsizing the organization. From the aspect of integrating people (apparatus HR management), the needs of employees in the Office are not following the organization's requirements. Based on these findings, this study concludes that the Office's functions in managing constituent aspirations are not optimal due to failure to meet two of the three rightsizing requirements for the office organization.